Effectiveness of the Line Probe Assay Compared with Conventional Culture for Detecting Second-Line Anti-Tuberculosis Drug Resistance - Aristoteles Aristoteles; Nurhidayanti Nurhidayanti (Direktorat Politeknik Kesehatan Makassar, 2025)
Drug-resistant tuberculosis (MDR-TB and rifampicin-resistant TB) is a major challenge in TB control in Indonesia. Rapid detection of second-line anti-TB drug resistance is crucial for timely initiation of therapy. Line Probe Assay (LPA) is a molecular method recommended by WHO as an alternative to conventional culture tests such as Mycobacterium Growth Indicator Tube (MGIT) and Lowenstein Jensen, which have longer detection times. This research aimed to determine the effectiveness of the time and diagnostic efficiency of the Line Probe Assay method compared to conventional cultures (MGIT and Lowenstein Jensen) for identifying second-line anti-TB drug resistance in MDR-TB and rifampicin-resistant TB patients. This study employed an observational analytical design with a cross-sectional approach that incorporated a post-test-only control group framework to compare the performance of the Line Probe Assay (LPA) and conventional culture methods in detecting second-line anti-tuberculosis drug resistanceData were collected from two groups of patients: one group with multidrug-resistant tuberculosis (MDR-TB) and other with rifampicin-resistant TB. All samples were examined using the Line Probe Assay (LPA), Mycobacterium Growth Indicator Tube (MGIT), and Lowenstein-Jensen (LJ) culture methods. A total of 30 collected sputum specimens were analyzed based on the time of the results, ease of interpretation, and readiness for therapy. Findings indicated that the Line Probe Assay (LPA) provided results within 1–2 days, compared to Mycobacterium Growth Indicator Tube (MGIT) (average 17 days) and Lowenstein-Jensen (LJ) culture (average 28–42 days). LPA demonstrated higher efficiency in both laboratory workflow and clinical readiness for early therapeutic decision-making.For the MDR-TB group, LPA successfully detected resistance to fluoroquinolones (gyrA/gyrB mutations) and second-line injectable drugs such as amikacin and kanamycin (rrs/eis mutations), showing full concordance with culture results. Similarly, in the rifampicin-resistant TB group, LPA identified additional resistance patterns consistent with culture findings, confirming its broad applicability for detecting second-line drug resistance. Although the diagnostic accuracy of all three methods was equally high (100% sensitivity and specificity), LPA was clearly superior in terms of turnaround time and overall laboratory efficiency. This study concludes that the Line Probe Assay is more effective and efficient than conventional culture methods for identifying second-line anti-TB resistance in MDR-TB and rifampicin-resistant TB patients, and is strongly suggested for initial screening to accelerate clinical management.